2019
DOI: 10.1093/mnras/stz1811
|View full text |Cite
|
Sign up to set email alerts
|

The case for a high-redshift origin of GRB 100205A

Abstract: The number of long gamma-ray bursts (GRBs) known to have occurred in the distant Universe (z > 5) is small (∼15), however these events provide a powerful way of probing star formation at the onset of galaxy evolution. In this paper, we present the case for GRB 100205A being a largely overlooked high-redshift event. While initially noted as a high-z candidate, this event and its host galaxy have not been explored in detail. By combining optical and near-infrared Gemini afterglow imaging (at t < 1.3 days since b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Furthermore, the burst lay behind a complex region of Galactic dust, making the foreground extinction for this event high but also poorly determined (Tanvir et al 2006). Then, Chrimes et al (2019) report on observations of GRB 100205A, which had an afterglow that was yet again significantly fainter than that of GRB 090429B, and no reasonably precise photo-z could be determined, but it could lie at up to z ≈ 8.…”
Section: The High-redshift Samplementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the burst lay behind a complex region of Galactic dust, making the foreground extinction for this event high but also poorly determined (Tanvir et al 2006). Then, Chrimes et al (2019) report on observations of GRB 100205A, which had an afterglow that was yet again significantly fainter than that of GRB 090429B, and no reasonably precise photo-z could be determined, but it could lie at up to z ≈ 8.…”
Section: The High-redshift Samplementioning
confidence: 99%
“…We therefore conclude there is no evidence for significant afterglow luminosity evolution between z ≳ 6 to 1.4 < z ≲ 6. Now, the problem that arises is that most z ≳ 6 GRB afterglows have only been observed, and have only really been observable, by large ( / ⃝ ≳ 2 m) telescopes with NIR capabilities, such as the 2.2 m MPG/GROND, the 3.8 m United Kingdom InfraRed Telescope (UKIRT)/Wide Field Infrared Camera (WFCAM; Casali et al 2007), and "big glass" such as the 8.2 m VLT/(ISAAC or HAWKI), 8.1 m Gemini/NIRI, and 10.0 m Keck/MOSFIRE (Chrimes et al 2019). This implies that few high-z GRB afterglows (specifically the aforementioned, very luminous GRBs 050904, 130606A, as well as, with some extrapolation, GRBs 080913, 210905A) have actually been detected during the time after trigger that Gamow will be attaining its first finding chart; and this sample is very clearly biased toward the most luminous high redshift events as only those have been detectable by rapidly slewing telescope robots of small aperture.…”
Section: The High-redshift Samplementioning
confidence: 99%
“…With the rapid slewing capabilities of Swift, observations with Swift/UVOT have enabled us to rule out these dark GRBs as being due to factors such as a lack of sensitivity, late observation times, and rapid temporal decays [173]. The low detection rate or "darkness", could however, be due to one or more of the following: a high background due to a small Sun-to-field angle [174], a large galactic extinction (e.g., [174,175]), a high circumburst extinction (e.g., [176][177][178]), intrinsic faintness [177], and Lyα damping due to high redshift (e.g., [176,177,179]). Several studies, including those using Swift/UVOT observations (e.g., [72]), have suggested that high circumburst extinction and high-redshift are the two main causes for why GRBs are 'dark' [67,172,173,180].…”
Section: Dark Grbsmentioning
confidence: 99%